Answer:
[tex]i ( e^{t} - e^{-t})+ j (cost-sin t)+ k (-15t^{2})[/tex]
Step-by-step explanation:
Step 1:-
Given c1(t) = e^ t i + (sin(t))j + t^3k
and c2(t) = e^−t i + (cos(t))j − 6t^3k.
adding c1(t)+c2(t) = e^ t i + (sin(t))j + t^3k+ e^−t i + (cos(t))j − 6t^3k
by using derivative formula
[tex]\frac{d}{dx}(e^x) = e^x[/tex]
[tex]\frac{d}{dx}(sinx) = cosx\\\frac{d}{dx}(cosx) = -sinx[/tex]
now differentiating with respective to 't'
[tex]\frac{d}{dt}c_{1}+ c_{2} } = e^ t i +cost j +3t^2 k - e^-t i - sintj -18t^2 k[/tex]
taking common i, j and k terms ,we get
[tex]\frac{d}{dt}(C_{1} +C_{2} ) = i ( e^{t} - e^{-t})+ j (cost-sin t)+ k (-15t^{2})[/tex]